2010
DOI: 10.1016/j.infbeh.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on early movement: Tykes, togs, and technology

Abstract: Examining the effects of diapers and other external constraints on infants' leg movements may affect how we collect motor control research data, dress infants to allow optimal movement in the home, and administer therapeutic interventions for infants with motor impairments. To address this issue we supported 12 healthy infants (2-4 months) on an infant-sized treadmill in each of 4 conditions: wearing nothing (None), a swim diaper (Swim), a disposable diaper (Diaper), or a combination of diaper and research rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…For example, in cold weather, it is typically necessary to use many layers of clothing to bundle up infants, which can constrain their movement. Groenen, Kruijsen, Mulvey and Ulrich [ 47 ] maintain that wearing bulky clothes in infancy can constrain movement sufficiently to delay exploration and performance of motor skills. This same restrictive clothing may mean that infants are also not exposed to enough stimulation by touch, which can result in both cognitive and psychomotor delays.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in cold weather, it is typically necessary to use many layers of clothing to bundle up infants, which can constrain their movement. Groenen, Kruijsen, Mulvey and Ulrich [ 47 ] maintain that wearing bulky clothes in infancy can constrain movement sufficiently to delay exploration and performance of motor skills. This same restrictive clothing may mean that infants are also not exposed to enough stimulation by touch, which can result in both cognitive and psychomotor delays.…”
Section: Discussionmentioning
confidence: 99%
“…The current study provides a cautionary note for researchers because many have not reported what infants were wearing (Bril & Breniere, 1989; Shirley, 1931). Clothes, shoes, and recording devices can affect infants’ movements: Pre‐walking 2‐ to 4‐month‐olds showed equal frequency of alternating upright steps while naked or wearing a diaper, but tight leggings of the sort typically worn to facilitate high‐speed motion tracking impeded their movements (Groenen et al ., 2010). Lack of information about infants’ diapers and other garb is particularly worrisome when attempting to interpret historical changes and cross‐cultural differences in walking skill.…”
Section: Discussionmentioning
confidence: 99%
“…In the 19th century, 40% of American infants skipped crawling, possibly because their long flowing gowns impeded movement on hands and knees (Trettien, 1900). More recently, infants who wear thick winter clothes or sleep under heavy blankets show delays in prone skills such as crawling (Bensen, 1993; Hayashi, 1992), and tight leggings reduce the frequency of upright stepping movements in 2‐ to 4‐month‐olds (Groenen, Kruijsen, Mulvey & Ulrich, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Inter-limb coordination was determined using criteria that were similar to those developed by Groenen, Kruijsen, Mulvey, and Ulrich (2010). Parallel steps were defined as steps initiated between the beginning and 20% of a step cycle on the opposite leg.…”
Section: Defining Amentioning
confidence: 99%